Plan de negocios para la importación de esponjas con nano partículas de cobre para la limpieza de utensilios de cocina desde Chile a Ecuador y para comercialización en la ciudad de Quito - Tapia Muela, Johanna Lucia (2016)
Tecsponge CIA. Ltda. is trying to be introduced to the market by this project. The purpose is to import and sell sponges with cooper nanoparticles from Chile to Ecuador, because these sponges kill 99.9% of retained sponges in normal bacteria. Thanks to nanotechnology cooper can be incorporated along with nanoparticle and fiber sponge with antibacterial properties, their durability is higher than traditional sponges and fully recyclable so it does not pollute the environment. This sponge will be sell to housewives between 20 to 65 years old in Quito. Nowadays, the market has a lot of competition but the main competition are manufacturers of sponges normal fiber and designed to protect nails housewives and scratches on cookware, but they do not have antibacterial properties. After making the marketing plan, it was determined that our principal differentiator is nanotechnology and its antibacterial benefits; it has been determined that the best way to distribute sponges is through supermarkets, especially Supermaxi. The import process of sponges will be made by an agent and will last 23 days counting all the requirements for being an importer, the company team is a General Manager and a Financial Manager Marketing and Sales, a Manager of winery will and a driver. The main financial indicators obtained are: NPV of $ 39,303.94 and a positive rate of return of 56.54% which shows that the project is viable.